2021
DOI: 10.1109/jeds.2021.3116975
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Modeling of Self-Heating in Nanometer Bulk-CMOS at Cryogenic Temperatures

Abstract: This work presents a self-heating study of a 40nm bulk-CMOS technology in the ambient temperature range from 300 K down to 4.2 K. A custom test chip was designed and fabricated for measuring both the temperature rise in the MOSFET channel and in the surrounding silicon substrate, using the gate resistance and silicon diodes as sensors, respectively. Since self-heating depends on factors such as device geometry and power density, the test structure characterized in this work was specifically designed to resembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…5 shows that the self-heating temperature rise model of Eq. ( 7) reproduces reasonably well the ∆T(P,T) data of [6] for 40nm bulk MOSFETs operated at deep cryogenic temperatures.…”
Section: Figsupporting
confidence: 63%
See 2 more Smart Citations
“…5 shows that the self-heating temperature rise model of Eq. ( 7) reproduces reasonably well the ∆T(P,T) data of [6] for 40nm bulk MOSFETs operated at deep cryogenic temperatures.…”
Section: Figsupporting
confidence: 63%
“…CMOS devices recently reported by Hart et al [6] and shown in Fig 5 (red solid lines). They found that the differential thermal resistance deduced from ∆T(P,T) data can also be fitted by an equation of the form, * = ) ,…”
Section: Figmentioning
confidence: 85%
See 1 more Smart Citation
“…13), showing intermodulation products <-30dBc, sufficient for a 99.99% readout fidelity [39]. The measured receiver noise temperature is 44K, which we believe might be limited by device self-heating [42]. Analysis of readout fidelity based on receiver noise figure and other parameters can be found in [39].…”
Section: State Of the Art Reviewmentioning
confidence: 92%
“…In both cases, electromagnetic and thermal crosstalk from the electronics must be tightly controlled not to spoil qubit performance. For instance, cryogenic self-heating from CMOS transistors can significantly affect the temperature of on-chip devices even at tens of μm distance [42], thus potentially limiting the integration density of such a quantum/classical system. As sketched above, the path towards the integration of the cryogenic electronic interface to support large-scale quantum processors will still require significant innovations.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%